Complicated postoperative course secondary to kratom withdrawal: a case report - Kucharik, Michael (J Surg Case Rep, 2019)
We herein report a case of a 55-year-old female with an unusual case of post-operative kratom withdrawal. The patient’s withdrawal symptoms subsequently contributed to complications and admission to the intensive care unit. Features of this case are discussed, alongside the management of kratom withdrawal and the implications of supplementation with unregulated herbal medications.